Muslim customer perceived value (MCPV) and tourists' travel decision making in purchasing Islamic tour package / Nurafiqah Mohamad Musa - Mohamad Musa, Nurafiqah (2017)
As the Muslim population is growing rapidly, Muslim consumer market should be critically concerned by businesses to satisfy the needs and wants of consumers. The current study attempted to investigate the relationship between Muslim customer perceived values (MCPV) and tourists' travel decision making. Islamic religiosity is the moderating variable in the study to examine its influence towards MCPV and tourists' travel decision making. The researcher focuses on the influence of Islamic religiosity towards maqasid shariah which is the Islamic value dimensions and tourists' travel decision making in order to intensely understand the power of level of religiosity among Muslims in their travel decision making towards travel packages. However, Islamic religiosity only wanted to see its influence towards Islamic value dimensions as adapted from previous research. A total of 396 respondents, consisting of Malaysian Muslim tourists who had purchased Islamic travel package were obtained through convenient sampling. Questionnaires were blasted through online survey by using Google form. Throughout the study, it has been identified that MCPV has significant relationship with tourists' travel decision making. Islamic religiosity only moderates the relationship between protection of religion and tourists' travel decision making. The results of the study can be beneficial for their marketing strategies and for future planning. The acknowledgment of such value dimensions can facilitate tourism industry to grow more well-developed positioning strategy